Potensi Rush Money dalam Pertimbangan Melakukan Audit Eksternal Lembaga Perkreditan Desa - I Made Sara (Universitas Pendidikan Ganesha, 2021)
The purpose of this study was to examine the influence of the variable ownership, size (size), potential rush money and supervision of the need for an external audit at village credit institutions. This research was conducted in all LPDs in Bali Province with a population of 1,327 LPDs, but the samples were 93 institutions. Data collection was carried out by survey using a questionnaire. And the collected data were analyzed using multiple linear regression method. The result is that the LPD ownership and size variables do not have a significant effect on the LPD's decision to conduct an external audit, because the need for an external audit is only done when the LPD experiences a case of fraud or loss of customer funds or other cases related to fraud. meanwhile, the variables of potential for rush money and supervision have a positive and significant effect on the need for an external audit. This happened because of the various financial cases that occurred in financial institutions the most feared thing was rush money, so it needed to be prevented, so that once fraud was detected in the LPD, an external audit was immediately carried out to maintain public trust in the institution. Next is supervision, this is of course closely related to the LPD's decision to carry out an external audit or not, because supervision by the supervisory agency has a detection and prevention function in the act of financial fraud.